Formulation and evaluation of opthalmic insert drug delivery system of forskolin - Wagh, Vijay D; Wagh, Kalpana V; Patil, Prangya P; Samanta, Malay K (Asian Journal of Pharmaceutics (AJP), 2014)
Forskolin, a diterpene obtained from natural roots of Coleus forskohlii (wild) Briq. (family: Lamiaceae), reduces intraocular pressure (IOP) by 23-28%, which is a desirable feature for an antiglaucoma therapy. Polyvinyl alcohol-14000 based ophthalmic inserts of pure forskolin (PVA-OIF) were prepared as matrix drug delivery with the aim of achieving once a day administration. Ophthalmic inserts were prepared using polymer PVA in various concentrations. The ophthalmic inserts were evaluated for evaluation parameters and in vitro drug release. One-way ANOVA tested in vitro release characteristics statistically. The in vitro release data was treated according to diffusion model proposed by Higuchi and Peppas in order to access the mechanism of drug release. The batch formulated with PVA-14000 (1.5%), showed sustained drug release behavior over a period of 6 hrs.